Factors influencing observation of standard precautions among nursing staff in tertiary care setting in Mangalore - Rashmi, Anusha; Kundapur, Rashmi (International Journal Of Community Medicine And Public Health, 2017)
Background: Health care professionals and particularly nurses are often exposed to microorganisms, many of which can cause serious infections. Although the potential for HBV transmission in the workplace setting is greater than for HIV, the mode of transmission for these two viruses are the same. Because of the environment in which they work, many health care workers are at an increased risk of accidental needle stick injuries (NSI) and blood borne pathogens such as HIV, Hep B, and HCV. The objectives of the study were to assess the knowledge, attitude and practice of standard precautions among nursing staff working in 5 tertiary care hospitals attached to teaching institutions in Mangalore and to assess the factors associated with non-compliance with standard precautions among nurses Methods: The study was done in 5 tertiary care hospitals attached to teaching institutions in Mangalore among the working nursing staff in these hospitals. A pre-tested questionnaire was used to collect the information regarding knowledge, attitude and practice and the reasons for non-adherence to standard precautions. Results: Regarding standard precautions 66.7% had a good knowledge, 74.7% had good practice and 87.3% had a positive attitude towards it. 26.34% attributed noncompliance to excess workload. Increasing age and increase in duration of nursing practice showed a significant increase in KAP scores. Conclusions: The duration of nursing practice influenced the knowledge and the compliance to standard precautions.